A conductive bus bar and its preparation method and application

CN123018362APending Publication Date: 2026-10-30BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610967820.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,单纯依靠增加截面积的方式会带来明显的负面效应:一方面会导致汇流排自身重量显著增加,不利于整车或设备的轻量化设计;另一方面会加剧电池包或电气机柜内部空间的占用,限制了功率密度和系统集成的紧凑性

Benefits of technology

[0024]本公开实施例提供的技术方案与现有技术相比具有如下优点:

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present disclosure relates to the technical field of battery module, and particularly relates to a conductive busbar and a preparation method and application thereof. The conductive busbar comprises a body segment and end overlap segments respectively located on both sides of the body segment, and the body segment and the end overlap segments comprise a copper base and graphene dispersed in the copper base. The present disclosure selects graphene with excellent electrical conductivity, thermal conductivity and mechanical properties as an additive for reinforcing the copper-based material, thereby enhancing the electrical conductivity of the obtained conductive busbar. Compared with a pure copper busbar, the electrical conductivity is improved by more than 6%. The conductive busbar disclosed by the present disclosure is particularly suitable for use in a super-fast charging battery system or other locations and occasions with high demand for conductive overcurrent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of battery module technology, and in particular to a conductive bus, its preparation method and application. Background Technology

[0002] Conductive busbars, as key components for power transmission and distribution, are widely used in power transmission and transformation systems, industrial power distribution equipment, new energy vehicle power batteries, and smart terminals (such as robots and smart homes). Currently, commercially available conductive busbars are mainly made of pure copper and pure aluminum. Due to limitations such as material purity, work hardening, and the introduction of impurities, the conductivity of existing copper busbars generally does not exceed 100% IACS (International Annealed Copper Standard), and in practical applications, it is often lower than this value, making it difficult to break through the upper limit of the intrinsic conductivity of pure copper.

[0003] In high-current applications (such as electric vehicle battery modules, high-power energy storage systems, and rail transit traction converters), to meet rated current carrying capacity and temperature rise requirements, it is usually necessary to increase the cross-sectional area of ​​the busbar to reduce resistance and increase current carrying capacity. However, simply increasing the cross-sectional area has significant negative effects: on the one hand, it leads to a significant increase in the weight of the busbar itself, which is not conducive to the lightweight design of the whole vehicle or equipment; on the other hand, it increases the space occupied inside the battery pack or electrical cabinet, limiting power density and the compactness of system integration.

[0004] Therefore, how to improve the overall conductivity of conductive busbars while meeting the application requirements for weight and volume has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] To address the aforementioned technical problems, this disclosure provides a conductive bus, its preparation method, and its application.

[0006] In a first aspect, this disclosure provides a conductive bus, including a body segment and end overlap segments located on both sides of the body segment, wherein the body segment and the end overlap segments include a copper substrate and graphene dispersed in the copper substrate.

[0007] As a preferred technical solution of this disclosure, with the total mass of the copper matrix and the graphene being 100%, the mass content of the graphene is 0.1%-1%.

[0008] As a preferred technical solution of this disclosure, the graphene has an average sheet diameter of 15-35 μm and a number of layers ≤ 5.

[0009] As a preferred technical solution of this disclosure, the conductive bus further includes an insulating layer disposed on the outer surface of the body section, the insulating layer including an epoxy resin coating or a heat shrink tubing layer.

[0010] In a second aspect, this disclosure provides a method for preparing a conductive bus as described in the first aspect, the method comprising the following steps: (1) Graphene is subjected to activation treatment, chemical copper plating treatment and electroplating copper treatment in sequence to obtain modified graphene, wherein the modified graphene includes graphene and a copper layer coated on the surface of the graphene. (2) The modified graphene obtained in step (1) is mixed with copper powder to obtain a mixed powder; the mixed powder is then subjected to pressing, sintering, densification and shaping and drilling processes to obtain a conductive busbar.

[0011] As a preferred technical solution of this disclosure, the activation treatment in step (1) includes: mixing the graphene with an oxidant for activation treatment, so that oxygen-containing functional groups are introduced on the surface of the graphene. The oxidant includes concentrated sulfuric acid, and the mass concentration of the concentrated sulfuric acid is 95-98%.

[0012] As a preferred technical solution of this disclosure, the chemical copper plating process in step (1) includes: placing the activated graphene in a chemical copper plating solution and reacting for 30-60 minutes to coat its surface with a copper layer; the chemical copper plating solution includes: CuSO4·5H2O 5-10g / L, complexing agent 20-30g / L, reducing agent 10-15mL / L and alkali, with a pH of 11-12.

[0013] As a preferred technical solution of this disclosure, the complexing agent includes sodium potassium tartrate, the reducing agent includes formaldehyde, and the alkali includes sodium hydroxide.

[0014] As a preferred technical solution of this disclosure, the copper plating process in step (1) adopts an alkaline pyrophosphate copper plating system + suspension electroplating technology.

[0015] Specifically, the process includes: dispersing the graphene treated with the chemical copper plating in an alkaline pyrophosphate copper plating solution, suspending it by mechanical stirring, using a stainless steel plate as the cathode and an oxygen-free copper plate as the anode, applying a direct current to make the cathode current density 1–2 A / dm², electroplating for 30–60 min, maintaining suspension and stirring during the process, so that copper ions are deposited on the surface, thereby thickening the copper layer.

[0016] The alkaline pyrophosphate copper plating solution comprises: 60–80 g / L copper pyrophosphate, 280–350 g / L potassium pyrophosphate, 10–25 g / L ammonium citrate, and ammonia water, with a pH of 8.2–8.8.

[0017] As a preferred technical solution of this disclosure, the thickness of the copper layer in the modified graphene is 0.5-1 μm.

[0018] As a preferred technical solution of this disclosure, the raw materials added during mixing in step (2) also include a lubricant, which includes carbon powder.

[0019] As a preferred technical solution of this disclosure, the pressing and molding in step (2) includes: placing the mixed powder in a mold and pressing it under a pressure of 500-600MPa to obtain a blank.

[0020] As a preferred technical solution of this disclosure, the sintering temperature in step (2) is 900-1000℃ and the time is 1-2h.

[0021] As a preferred technical solution of this disclosure, the densification and shaping process in step (2) includes forging, wherein the forging pressure is 200-300MPa and the temperature is 800-900℃.

[0022] As a preferred technical solution of this disclosure, the preparation method further includes: covering the outer surface of the body section of the obtained conductive bus with an insulating layer.

[0023] Thirdly, this disclosure provides a battery module, including a conductive bus as described in the first aspect or a conductive bus prepared by the preparation method described in the second aspect.

[0024] The technical solution provided in this disclosure has the following advantages compared with the prior art: This disclosure selects graphene, which has excellent electrical conductivity, thermal conductivity and mechanical properties, as an additive to enhance the conductivity of the obtained conductive bus. Compared with pure copper bus, the conductivity is increased by more than 6%. Furthermore, by plating copper on its surface, the dispersion uniformity of graphene in the copper matrix is ​​improved, and its bonding force with the copper metal matrix is ​​increased.

[0025] The conductive bus described in this disclosure is applicable to super-fast charging battery systems or other locations and applications with high requirements for conductivity and overcurrent. Detailed Implementation

[0026] To better understand the above-mentioned objectives, features, and advantages of this disclosure, the solutions disclosed herein will be further described below. It should be noted that, unless otherwise specified, the embodiments and features described herein can be combined with each other.

[0027] Numerous specific details are set forth in the following description in order to provide a full understanding of this disclosure, but this disclosure may also be implemented in other ways different from those described herein; obviously, the embodiments in the specification are only some, and not all, of the embodiments of this disclosure.

[0028] In a first aspect, this disclosure provides a conductive bus, including a body segment and end overlap segments located on both sides of the body segment, wherein the body segment and the end overlap segments include a copper substrate and graphene dispersed in the copper substrate.

[0029] This disclosure selects graphene, which has excellent electrical conductivity, thermal conductivity and mechanical properties, as an additive to enhance the conductivity of the obtained conductive bus, which is more than 6% higher than that of pure copper bus.

[0030] In this disclosure, at least five 20μm × 20μm regions were taken from the cross-section of the conductive bus for EDS surface scanning, and the mass percentage of characteristic elements (carbon) in the dispersed phase (graphene) was statistically analyzed, with a relative standard deviation (RSD) ≤ 8%. This indicates that the graphene is uniformly dispersed in the copper matrix.

[0031] In some embodiments, the graphene content is 0.1%-1% based on the total mass of the copper matrix and the graphene as 100%, such as 0.1%, 0.2%, 0.5% or 1%, but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0032] In this disclosure, selecting an appropriate amount of graphene helps ensure the mechanical properties and conductivity of the resulting conductive busbar. Excessive addition can cause graphene agglomeration, leading to a decrease in the conductivity and mechanical properties of the finished product.

[0033] In some embodiments, the average sheet diameter of the graphene is 15-35 μm and the number of layers is ≤5. For example, the average sheet diameter can be 15 μm, 20 μm, 25 μm, 30 μm or 35 μm, etc., and the number of layers can be 1 layer, 2 layers, 3 layers, 4 layers or 5 layers, etc., but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0034] In this disclosure, selecting graphene of appropriate specifications helps to ensure the overall conductivity of the conductive bus.

[0035] In some embodiments, an insulating layer is provided on the outer surface of the body section of the conductive bus.

[0036] In some embodiments, the insulating layer includes an epoxy resin coating or a heat-shrink tubing layer.

[0037] In some embodiments, the body segment and the end overlap segment further include a lubricant dispersed in the copper substrate, the lubricant comprising carbon.

[0038] In a second aspect, this disclosure provides a method for preparing a conductive bus as described in the first aspect, the method comprising the following steps: (1) Graphene is subjected to activation treatment, chemical copper plating treatment and electroplating copper treatment in sequence to obtain modified graphene, wherein the modified graphene includes graphene and a copper layer coated on the surface of the graphene. (2) The modified graphene obtained in step (1) is mixed with copper powder to obtain a mixed powder; the mixed powder is then subjected to pressing, sintering, densification and shaping and drilling processes to obtain a conductive busbar.

[0039] The preparation method described in this disclosure effectively solves the shortcomings of graphene's poor dispersibility and easy agglomeration during conductive bus processing by activating graphene and then plating it with copper (including chemical plating and electroplating). Furthermore, copper plating enhances its adhesion to the copper metal substrate. Compared with traditional copper plate stamping processes for preparing conductive buses, the powder metallurgy process generates no waste, achieving a 100% material utilization rate.

[0040] In some embodiments, the activation process in step (1) includes: activating the graphene by mixing it with an oxidant to introduce oxygen-containing functional groups onto the surface of the graphene. The oxidizing agent includes concentrated sulfuric acid, the mass concentration of which is 95%-98%, such as 95%, 96%, 97% or 98%, but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0041] This disclosure introduces active sites (i.e., oxygen-containing functional groups, such as hydroxyl and carboxyl groups) on the surface of graphene through activation treatment, thereby solving the problems of hydrophobicity and easy aggregation of graphene, while ensuring the uniformity of subsequent copper plating.

[0042] In some embodiments, the activated graphene is dispersed in deionized water for later use. Preferably, a dispersant is also added to the deionized water.

[0043] In some embodiments, the electroless copper plating process in step (1) includes: placing the activated graphene in an electroless copper plating solution and reacting for 30-60 minutes to coat its surface with a copper layer; the electroless copper plating solution includes: CuSO4·5H2O 5-10 g / L, complexing agent 20-30 g / L, reducing agent 10-15 mL / L and alkali, with a pH of 11-12.

[0044] The concentration of CuSO4·5H2O can be 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L, etc., but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0045] The concentration of the complexing agent can be 20 g / L, 22 g / L, 24 g / L, 26 g / L, 28 g / L or 30 g / L, but is not limited to the values ​​listed. Other values ​​not listed within the above range are also applicable.

[0046] The concentration of the reducing agent can be 10 mL / L, 11 mL / L, 12 mL / L, 13 mL / L, 14 mL / L or 15 mL / L, etc., but is not limited to the values ​​listed. Other values ​​not listed in the above range are also applicable.

[0047] In some embodiments, the complexing agent comprises sodium potassium tartrate, the reducing agent comprises formaldehyde, and the base comprises sodium hydroxide.

[0048] In some embodiments, the copper plating process in step (1) employs an alkaline pyrophosphate copper plating system combined with suspension electroplating technology.

[0049] Specifically, the process includes: dispersing graphene that has undergone chemical copper plating in an alkaline pyrophosphate copper plating solution, suspending it by mechanical stirring, using a stainless steel plate as the cathode and an oxygen-free copper plate as the anode, applying a direct current to make the cathode current density 1–2 A / dm², electroplating for 30–60 min, maintaining suspension and stirring during the process, so that copper ions are electrodeposited on the surface, thereby thickening the copper layer.

[0050] The current density can be 1 A / dm. 2 1.5A / dm 2 or 2A / dm 2 The values ​​listed are not limited to those listed; other unlisted values ​​within the above range also apply.

[0051] The electroplating time can be 30 min, 40 min, 50 min or 60 min, etc., but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0052] The alkaline pyrophosphate copper plating solution comprises: 60–80 g / L copper pyrophosphate, 280–350 g / L potassium pyrophosphate, 10–25 g / L ammonium citrate, and ammonia water, with a pH of 8.2–8.8.

[0053] The copper pyrophosphate concentration can be 60 g / L, 65 g / L, 70 g / L, 75 g / L, or 80 g / L, but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0054] Potassium pyrophosphate can be 280 g / L, 290 g / L, 300 g / L, 310 g / L, 320 g / L, 330 g / L, 340 g / L, or 350 g / L, but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0055] Ammonium citrate can be 10 g / L, 15 g / L, 20 g / L or 25 g / L, but is not limited to the values ​​listed. Other values ​​not listed within the above range are also applicable.

[0056] In some embodiments, the thickness of the copper layer in the modified graphene is 0.5-1 μm, such as 0.5 μm, 0.6 μm, 0.8 μm or 1 μm, but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0057] The copper layer thickness specified in this disclosure is sufficient to achieve the desired effect; excessive thickness will increase costs and reduce efficiency.

[0058] Furthermore, after completing the chemical copper plating and electroplating processes in step (1), the modified graphene obtained can be dried to prevent residues of electroplating solution, moisture, etc.

[0059] In some embodiments, the raw materials mixed in step (2) further include a lubricant, which includes carbon powder.

[0060] In this disclosure, a lubricant is added to reduce friction between powder particles and between the powder and the mold, thereby improving mixing uniformity, green density, and demolding performance, reducing pressing cracks, and to some extent protecting copper from excessive oxidation. However, the amount added should not be excessive, as too much will impair the product's electrical and thermal conductivity.

[0061] In some embodiments, the pressing process in step (2) includes: placing the mixed powder in a mold and pressing it under a pressure of 500-600 MPa to obtain a blank.

[0062] The pressure can be selected from 500MPa, 520MPa, 540MPa, 560MPa, 580MPa or 600MPa, etc., but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0063] In this disclosure, a density of 6.7~7.1 g / cm³ is obtained by pressing. 3 The blank.

[0064] In some embodiments, the sintering temperature in step (2) is 900-1000℃, such as 900℃, 950℃ or 1000℃; the time is 1-2h, such as 1h, 1.5h or 2h, but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0065] In this disclosure, high-temperature sintering is used to diffuse and bond powder particles in the blank, thereby improving electrical conductivity and mechanical properties. The sintering is performed under an inert atmosphere.

[0066] In some embodiments, the densification and shaping process in step (2) includes forging, wherein the forging pressure is 200-300 MPa, such as 200 MPa, 220 MPa, 240 MPa, 260 MPa, 280 MPa or 300 MPa, etc.; and the temperature is 800-900℃, such as 800℃, 820℃, 840℃, 860℃ or 900℃, etc., but is not limited to the listed values, and other unlisted values ​​within the above range are also applicable.

[0067] In this disclosure, the sintered billet is further subjected to densification and shaping treatment (such as forging) to achieve a density of 8.6 g / cm³. 3 The conductivity can reach 106% IACS or higher.

[0068] In some embodiments, the punching process includes punching holes in the end overlap section of the resulting conductive bus.

[0069] In some embodiments, the preparation method further includes: coating the outer surface of the body segment of the obtained conductive bus with an insulating layer.

[0070] Thirdly, this disclosure provides a battery module, including a conductive bus as described in the first aspect or a conductive bus prepared by the preparation method described in the second aspect.

[0071] The following explanation is provided through specific examples.

[0072] Unless otherwise specified, all raw materials used in the following examples are commercially available.

[0073] Example 1 This embodiment provides a conductive bus and its preparation method. The conductive bus includes a body segment and end overlap segments located on both sides of the body segment. The body segment and the end overlap segments include a copper substrate and graphene dispersed in the copper substrate. The graphene has an average sheet diameter of 20 μm and ≤5 layers. With the total mass of the copper matrix and the graphene being 100%, the mass content of the graphene is 1%.

[0074] The preparation method includes: (1) Graphene was activated by mixing it with concentrated sulfuric acid with a mass concentration of 98% to introduce oxygen-containing functional groups on the surface of graphene; the activated graphene was then dispersed in deionized water for later use. (2) The activated graphene was placed in a chemical copper plating solution and reacted for 60 min to deposit a copper layer on its surface; then it was dispersed in an alkaline pyrophosphate copper plating solution, and mechanical stirring was turned on to suspend it. A stainless steel plate was used as the cathode and an oxygen-free copper plate was used as the anode. A DC current was applied to make the cathode current density 1.5 A / dm², and electroplating was carried out for 40 min. During this period, the suspension and stirring were maintained to allow copper ions to be electrodeposited on the surface, thereby thickening the copper layer and obtaining modified graphene with a total copper layer thickness of 1 μm. The electroless copper plating solution includes: CuSO4·5H2O 8g / L, potassium sodium tartrate 22g / L, formaldehyde 13mL / L and NaOH, with a pH of 11. The alkaline pyrophosphate copper plating solution consists of: 70 g / L copper pyrophosphate, 300 g / L potassium pyrophosphate, 15 g / L ammonium citrate, and ammonia water, with a pH of 8.5. (3) The modified graphene was mixed with copper powder to obtain a mixed powder; the mixed powder was placed in a mold and pressed into a blank using a pressure of 450 MPa. The density of the resulting blank was 6.9 g / cm³. 3 ; (4) Place the obtained billet in a sintering furnace and sinter at 900℃ for 1 hour to obtain a sintered billet; (5) The sintered body was forged at 850℃ and subjected to a pressure of 250MPa to obtain a density of 8.9 g / cm³. 3 Forged billets; (6) Drill holes in the end overlap section of the forged billet to obtain a conductive busbar.

[0075] Example 2 This embodiment provides a conductive bus and its preparation method. The conductive bus includes a body segment and end overlap segments located on both sides of the body segment. The body segment and the end overlap segments include a copper substrate and graphene dispersed in the copper substrate. The graphene has an average sheet diameter of 35 μm and ≤5 layers. With the total mass of the copper matrix and the graphene being 100%, the mass content of the graphene is 0.5%.

[0076] The preparation method includes: (1) Graphene was activated by mixing it with concentrated sulfuric acid with a mass concentration of 98% to introduce oxygen-containing functional groups on the surface of graphene; the activated graphene was then dispersed in deionized water for later use. (2) The activated graphene was placed in a chemical copper plating solution and reacted for 30 min to deposit a copper layer on its surface; then it was dispersed in an alkaline pyrophosphate copper plating solution, and mechanical stirring was turned on to suspend it. A stainless steel plate was used as the cathode and an oxygen-free copper plate was used as the anode. A DC current was applied to make the cathode current density 1 A / dm², and electroplating was carried out for 60 min. During this period, the suspension and stirring were maintained to allow copper ions to be electrodeposited on the surface, thereby thickening the copper layer and obtaining modified graphene with a total copper layer thickness of 0.8 μm. The electroless copper plating solution includes: CuSO4·5H2O 6g / L, potassium sodium tartrate 25g / L, formaldehyde 12mL / L and NaOH, with a pH of 12. The alkaline pyrophosphate copper plating solution consists of: 65 g / L copper pyrophosphate, 320 g / L potassium pyrophosphate, 20 g / L ammonium citrate, and ammonia water, with a pH of 8.5. (3) The modified graphene was mixed with copper powder to obtain a mixed powder; the mixed powder was placed in a mold and pressed into a blank using a pressure of 500 MPa. The density of the resulting blank was 7.1 g / cm³. 3 ; (4) Place the obtained billet in a sintering furnace and sinter at 950°C for 2 hours to obtain a sintered billet; (5) The sintered body was forged at 900℃ and subjected to a pressure of 300MPa to obtain a density of 9.2 g / cm³. 3 Forged billets; (6) Drill holes in the end overlap section of the forged billet to obtain a conductive busbar.

[0077] Example 3 This embodiment provides a conductive bus and its preparation method. The conductive bus includes a body segment and end overlap segments located on both sides of the body segment. The body segment and the end overlap segments include a copper substrate and graphene dispersed in the copper substrate. The graphene has an average sheet diameter of 15 μm and ≤5 layers. With the total mass of the copper matrix and the graphene being 100%, the mass content of the graphene is 0.8%.

[0078] An insulating layer, which is a heat-shrink tubing, is provided on the outer surface of the main body section of the conductive bus.

[0079] The preparation method includes: (1) Graphene was activated by mixing it with concentrated sulfuric acid with a mass concentration of 98% to introduce oxygen-containing functional groups on the surface of graphene; the activated graphene was then dispersed in deionized water for later use. (2) The activated graphene was placed in a chemical copper plating solution and reacted for 40 min to deposit a copper layer on its surface; then it was dispersed in an alkaline pyrophosphate copper plating solution, and mechanical stirring was turned on to suspend it. A stainless steel plate was used as the cathode and an oxygen-free copper plate was used as the anode. A DC current was applied to make the cathode current density 2A / dm², and electroplating was carried out for 30 min. During this period, the suspension and stirring were maintained to allow copper ions to be electrodeposited on the surface, thereby thickening the copper layer and obtaining modified graphene with a total copper layer thickness of 0.9 μm. The electroless copper plating solution includes: CuSO4·5H2O 10g / L, potassium sodium tartrate 20g / L, formaldehyde 10mL / L and NaOH, with a pH of 11. The alkaline pyrophosphate copper plating solution includes: 60 g / L copper pyrophosphate, 300 g / L potassium pyrophosphate, 18 g / L ammonium citrate and ammonia water, with a pH of 8.8; (3) Modified graphene is mixed with copper powder to obtain a mixed powder; the mixed powder is added to a mold and pressed into a blank using a pressure of 400 MPa, and the density of the resulting blank is 6.7 g / cm³. 3 ; (4) Place the obtained billet in a sintering furnace and sinter at 1000℃ for 1.5h to obtain a sintered billet; (5) The sintered body was forged at 800℃ and subjected to a pressure of 280MPa to obtain a density of 8.9 g / cm³. 3 Forged billets; (6) Drill holes in the end overlap section of the forged billet, and then cover the outer surface of the body section with heat-shrinkable conduit to obtain a conductive busbar.

[0080] Comparative Example 1 This comparative example provides a method for preparing a conductive bus, referring to Example 1, except that step (1) is omitted and modified graphene is replaced with graphene. Because the graphene surface was not modified (copper plated), it agglomerated severely during powder metallurgy, resulting in decreased mechanical properties and making it impossible to obtain products that meet the standards.

[0081] Comparative Example 2 This comparative example provides a conductive bus and its preparation method, referring to Example 1, except that the conductive bus is only a copper substrate; The preparation method is the same as in Example 1, except that step (1) is not performed and the raw material for step (2) is only copper powder.

[0082] Performance testing Referring to the test results of the conductive busbars obtained in the examples and comparative examples according to GB / T 32791 standard, the conductivity of the conductive busbar in Comparative Example 2 (pure copper) was found to be 100% IACS, while the conductivity of the conductive buses obtained in Examples 1-3 of this disclosure all reached over 106% IACS. The conductive busbars described in this disclosure effectively improve the conductivity and current carrying capacity of copper busbars, reducing heat generation and energy loss caused by overcurrent.

[0083] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0084] The above description is merely a specific embodiment of this disclosure, enabling those skilled in the art to understand or implement it. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this disclosure. Therefore, this disclosure is not to be limited to the embodiments described herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A conductive bus, comprising a body section and end overlap sections respectively located on both sides of the body section, characterized in that, The body segment and the end overlap segment include a copper matrix and graphene dispersed in the copper matrix.

2. The conductive bus according to claim 1, characterized in that, With the total mass of the copper matrix and the graphene being 100%, the mass content of the graphene is 0.1%-1%.

3. The conductive bus according to claim 1 or 2, characterized in that, The graphene has an average sheet diameter of 15-35 μm and ≤5 layers.

4. The conductive bus according to any one of claims 1-3, characterized in that, The conductive bus also includes an insulating layer disposed on the outer surface of the body section, the insulating layer including an epoxy resin coating or a heat shrink tubing layer.

5. A method for preparing a conductive bus as described in any one of claims 1-4, characterized in that, The preparation method includes the following steps: (1) Graphene is subjected to activation treatment, chemical copper plating treatment and electroplating copper treatment in sequence to obtain modified graphene, wherein the modified graphene includes graphene and a copper layer coated on the surface of the graphene. (2) The modified graphene obtained in step (1) is mixed with copper powder to obtain a mixed powder; the mixed powder is then subjected to pressing, sintering, densification and shaping and drilling processes to obtain a conductive busbar.

6. The preparation method according to claim 5, characterized in that, The activation process in step (1) includes: activating the graphene by mixing it with an oxidant to introduce oxygen-containing functional groups onto the surface of the graphene; The oxidant includes concentrated sulfuric acid, and the concentrated sulfuric acid has a mass concentration of 95%-98%.

7. The preparation method according to claim 5 or 6, characterized in that, Step (1) The electroless copper plating process includes: placing the activated graphene in an electroless copper plating solution and reacting for 30-60 minutes to coat its surface with a copper layer; The electroless copper plating solution comprises: CuSO4·5H2O 5-10 g / L, complexing agent 20-30 g / L, reducing agent 10-15 mL / L and alkali, with a pH of 11-12.

8. The preparation method according to any one of claims 5-7, characterized in that, In the modified graphene, the thickness of the copper layer is 0.5-1 μm.

9. The preparation method according to any one of claims 5-8, characterized in that, The raw materials added during mixing in step (2) also include a lubricant, which includes carbon powder; And / or, the pressing molding in step (2) includes: placing the mixed powder in a mold and pressing it under a pressure of 500-600 MPa to obtain a blank; And / or, the sintering temperature in step (2) is 900-1000℃ and the time is 1-2h; And / or, the densification and shaping process in step (2) includes forging, wherein the forging pressure is 200-300 MPa and the temperature is 800-900 °C; And / or, the preparation method in step (2) further includes: covering the outer surface of the body segment of the obtained conductive bus with an insulating layer.

10. A battery module, characterized in that, This includes the conductive bus as described in any one of claims 1-4 or the conductive bus prepared by the preparation method described in any one of claims 5-9.